基于变性法加工的准双曲面齿轮齿面啮合分析 - 李明; 邓效忠 (Jixie chuandong)
The mathematical model of gear cutting machining of hypoid gear wheel forming,small modified method is set up.The basic form of modified expression is deduced and the initial value of modified coefficient is determined.The mathematical model of gear meshing is established.The influence of modified-roll coefficient on tooth surface meshing performance is studied by using the tooth surface detection technology.